Evolution of Bilateralism: A Historical Perspective on India-China Relations - Chaudhary, Seema (International Journal of Engineering and Management Research, 2023)
This paper explores how India-China ties have changed over time, from the brief era of friendly cohabitation represented by "Hindi-Chini Bhai Bhai" to the present strategic rivalry. It offers a historical examination of the major occasions and elements that have influenced bilateral relations, such as border conflicts, the Sino-Indian War of 1962, and changes in geopolitics. The paper explores the dynamics of the two countries' political, economic, and strategic interactions, emphasizing the growing rivalry in sectors including trade, infrastructure development, and regional influence. It also evaluates how these changing dynamics affect regional stability and the larger international order. The study looks at the difficulties and chances for collaboration in fields like commerce, international forums, and climate change. This paper seeks to shed light on the intricacies of the India-China relationship and its ramifications for the future by providing a thorough historical perspective. It ends with a discussion of possible strategies for controlling rivalry and encouraging positive interaction between these two superpowers.